Impact of Family Dysfunction on The Psychological Wellbeing of Pupils in Inclusive Schools in Lagos State, Nigeria - Omoshalewa Lasbat Badamas; Elizabeth O Uyanne; Ifinju I O (Journal of Educational Sciences, 2023)
Family plays a significant role on how children develop and a steady family that is steady (responsibility and functionality) is extremely important to the development of a child. A child's home environment should offer a favourable framework for healthy psychological wellbeing. Thus, this study investigated the impact of family dysfunction on the psychological wellbeing of pupils in inclusive schools in Lagos State. Descriptive survey research design was adopted for the study and simple random sampling technique was used to select 216 respondents from 12 inclusive schools in Lagos State. Two questionnaires titled Family Dysfunction and Psychological Wellbeing Scales (PWBS) were used. Percentage analysis was used to answer the research questions and PPMC was used to test the hypothesis at 0.05 alpha level. The study revealed that the level of family dysfunction among pupils in inclusive school in Lagos was relatively high, the state of psychological wellbeing of pupils in inclusive schools in Lagos was relatively low and there was significant negative impact of family dysfunction on psychological wellbeing of pupils in inclusive schools in Lagos State. The study concluded that social support (emotional support) should be highly encouraged by the school authorities to emotional support struggling pupils and their counterparts.